Pengaruh Kualitas Layanan Mikrotrans Jakarta Terhadap Kepuasan Penumpang - Hapsari, Meivina; Ramadhania Fitri, Afifa; Alfarel, Rio; Santoso, Daffa Dzakwan (Jurnal Sosial Teknologi, 2025)
The high mobility of Jakarta residents demands an efficient and integrated public transportation system. Microtrans as part of the JakLingko system becomes an important connecting transportation solution. This study aims to analyze the effect of Jakarta Microtrans service quality on passenger satisfaction using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. Data were collected through questionnaires from 125 active Microtrans users with a purposive sampling approach. Analysis was conducted based on five SERVQUAL dimensions: tangible, reliability, responsiveness, assurance, and empathy. The results show a CSI value of 84% which is in the "Very Satisfied" category. IPA analysis identified that drivers' ability to provide information and bus stop supporting facilities are top priorities for improvement (Quadrant I). Meanwhile, CCTV security aspects, responsiveness to priority passengers, and complaint services have performed well and need to be maintained (Quadrant II). There is a negative gap of -2.3 between expectations (54.7) and performance (52.4) indicating the need for service quality improvement. The reliability dimension has the highest negative gap (-1.7), while the tangible dimension shows the best performance with a positive gap of 5.7.